Design and fabrication of pressure jack / Muhammad Saiful Anuar Aminnudin and Syidatul Akma Sulaiman - Aminnudin, Muhammad Saiful Anuar; Sulaiman, Syidatul Akma (School of Mechanical Engineering, 2023)
Car jack is a mechanical device that help mechanic or people easier to lifting car for changing tyre and other operation involves car underpart. The problem that related to jacks are common problem associated with hydraulic jack is the screw requires high lubricant & easily getting stuck. Moreover, the jacks that car workshop has is not easy to carry and it cost a lot to service it. Thus, this problem can be settled by using pressure principle. The concept is still the same to lifting load but by using pneumatic piston and air compressor. The main goal of this project is to solve the problem with using pressure concept to replace the hydraulic concept, so it does not require any oil or fluid to work the jack. This project work using a jack with simple pressure principle using pneumatic piston and air compressor to push the piston up and lifting load and the outcome of this project is expected to be the product that can archive success and can do the innovation in jack.